Are preventive measures adequate? An evaluation of the implementation of COVID-19 prevention and control measures in nursing homes in China - Meihong Shi; Fengying Zhang; Xinxin He; Siyuan Huang; Mingfeng Zhang; Xiuying Hu (BMC, 2021)
Abstract Background The novel coronavirus disease 2019 (COVID-19) pandemic has become a challenge for nursing homes in China. Nursing homes are particularly dangerous places in terms of the spread of COVID-19 given that they house vulnerable, high-risk populations. As such, several useful guidelines for coping with COVID-19 in nursing homes have been provided. However, the actual implementation rates of such guidelines are unknown. This study aims to document the adherence of nursing homes to the Ministry of Civil Affairs guidelines for COVID-19 prevention and control in nursing homes. Methods A cross-sectional study was conducted among 484 nursing homes in 136 cities of 28 provinces in China. A self-report questionnaire was created based on the Ministry of Civil Affairs guidelines for COVID-19 prevention and control in nursing homes (first edition). The questionnaire and the Transformational Leadership in the Public Sector Scale were sent to nursing home managers via the Wenjuanxing app online from February 7 to 29, 2020. Ultimately, 461 of 960 nursing homes participated, for a response rate of 48.0%. Results The average overall implementation rate of COVID-19 prevention and control measures was 80.0% (143.97/180). The average implementation rates for hygienic behaviour management and access management were lower, at 75.3 and 78.7%, respectively. Number of medical staff and transformational leadership score of nursing home's manager were associated with total implementation score (p < 0.05). A total of 69.8% (322/461) of the nursing home managers had serious resource problems, and inadequate protective supplies (72.0%) and staff shortages (47.7%) were the two primary problems. The nursing homes that located in urban, with large nursing home size, had hospital-nursing home cooperation and the transformational leadership score of manager> 60, had a lower risk of having serious resource problems. Conclusions Overall, the implementation of prevention and control measures by nursing homes are insufficient during the epidemic in China. More medical staff, adequate resource, cooperation with hospitals, and higher transformational leadership of manager are required to improve the implementation rate. It is urgent for nursing homes to maintain the safety of residents and staff.